COMPOSIÇÃO E DIVERSIDADE DE ANFÍBIOS ANUROS (AMPHIBIA, ANURA) NO MATO DO SILVA, CHIAPETTA, RS - Follmann, Jéssica R.; Ferrazza, Tamires; Delasanta, Juliana; Marquezin, Graciela (Salão do Conhecimento, 2013)
Resumo